2019
DOI: 10.1103/physrevfluids.4.043902
|View full text |Cite
|
Sign up to set email alerts
|

Global linear instability of rotating-cone boundary layers in a quiescent medium

Abstract: The global linear stability of the family of infinite rotating-cone boundary layers in an otherwise still fluid is investigated using a velocity-vorticity form of the linearized Navier-Stokes equations. The formulation is separable with respect to the azimuthal direction. Thus, disturbance development is simulated for a single azimuthal mode number. Numerical simulations are conducted for an extensive range of cone half-angles (ψ ∈ [20 • : 80 • ]) and stability parameters (Reynolds number, azimuthal mode numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(117 reference statements)
2
5
0
Order By: Relevance
“…Also for broad cones stability theory has shown that an absolute instability exists (see, for instance, Refs. [10,11]), similar to the one for the disk as suggested by Lingwood [4]. However, since the stationary corotating vortices always exist in a physical experiment the role or importance of this absolute instability with respect to transition is not clear [12].…”
supporting
confidence: 52%
“…Also for broad cones stability theory has shown that an absolute instability exists (see, for instance, Refs. [10,11]), similar to the one for the disk as suggested by Lingwood [4]. However, since the stationary corotating vortices always exist in a physical experiment the role or importance of this absolute instability with respect to transition is not clear [12].…”
supporting
confidence: 52%
“…Numerical computations of the genuine inhomogeneous flow display global linear stability characteristics comparable with that found by Thomas and Davies 15,16 for the infinite rotating disc and family of rotating cones. A form of global linear instability, characterised by a faster than exponential growth, arises when the azimuthal mode number n exceeds a threshold value n g .…”
Section: Discussionsupporting
confidence: 74%
“…Thomas and Davies 15 also speculate that global linear instability exists for other related rotating flows. Their follow-up study 16 confirms this for the rotating cone boundary layer.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations